The effect of boron mineral on energy metabolism and antioxidant activity in purebred arabian foals - Guler-Ekmen, Edanur; Yilmaz, Ismail Cagri; Guler, Talat; Guler, Derya; Ozcelik, Mehtap (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Boron mineral is reported to have important functions in lipid and energy metabolism, immune and endocrine systems, and brain activity, positively affecting performance. This study investigated the effects of different doses of boron mineral (0, 5, 10, 15 mgd(-1)animal(-1)) at 30, 60, and 90 days on energy metabolism and antioxidant activity parameters in Purebred Arabian foals. The experiment was conducted on 32 foals, grouped randomly, with similar initial body weights, consisting of 8 foals per group (n=8). The experimental groups were defined by the doses of boron mineral administered. The control group (Group K) received no boron, Group B5 received 5 mg of elemental boron, Group B10 received 10 mg, and Group B15 received 15 mg per day per animal. Boric acid was used as the boron source. The study lasted 90 days. Feed consumption and body weight gain were similar across all groups (P>0.05). Throughout the study, no significant differences were detected in serum glucose, cholesterol, triglyceride, AST and ALT levels among the groups (P>0.05). MDA levels decreased dose-dependently after the initial measurements (P<0.001), while GSH-Px and CAT levels increased dose-dependently after the baseline measurements (P<0.001). In conclusion, boron mineral positively affected antioxidant activity in Purebred Arabian foals, with the most effective dose being 15 mgd(-1)animal(-1).
El efecto del mineral boro sobre el metabolismo energético y la actividad antioxidante en potros árabes de pura raza
Keywords: Boron; foals; energy metabolism; antioxidant level